2020
DOI: 10.33084/pengabdianmu.v5i2.1033
|View full text |Cite
|
Sign up to set email alerts
|

Pertanian Organik sebagai Salah Satu Konsep Pertanian Berkelanjutan

Abstract: Excessive use of inorganic chemicals results in adverse impacts on land and plants. In the midst of the community, there is anxiety about the high content of pesticide residues in agricultural products. There is a need to develop alternative farming systems that are able to produce quantities and quality of healthy products in a sustainable manner. One agricultural system that supports the concept is the organic farming system. The basic principles of organic farming are: (1) Keeping the ecosystem healthy, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
6
0
4
Order By: Relevance
“…Kesehatan pangan bagi manusia sangat berkorelasi dengan produk pangan yang dihasilkan secara organik sehingga praktik budidaya organik lebih baik daripada praktik budidaya secara konvensional (Mie et al, 2017). Produk-produk pertanian organik merupakan bahan pangan yang aman bagi kesehatan produsen dan konsumen serta tidak merusak lingkungan (Yuriansyah et al, 2020). Pertanian organik merupakan teknik budidaya pertanian yang berorientasi pada pemanfaatan bahan-bahan alami (lokal) tanpa menggunakan bahan-bahan kimia sintesis seperti pupuk dan pestisida (Rachma & Umam, 2020).…”
Section: Pendahuluanunclassified
“…Kesehatan pangan bagi manusia sangat berkorelasi dengan produk pangan yang dihasilkan secara organik sehingga praktik budidaya organik lebih baik daripada praktik budidaya secara konvensional (Mie et al, 2017). Produk-produk pertanian organik merupakan bahan pangan yang aman bagi kesehatan produsen dan konsumen serta tidak merusak lingkungan (Yuriansyah et al, 2020). Pertanian organik merupakan teknik budidaya pertanian yang berorientasi pada pemanfaatan bahan-bahan alami (lokal) tanpa menggunakan bahan-bahan kimia sintesis seperti pupuk dan pestisida (Rachma & Umam, 2020).…”
Section: Pendahuluanunclassified
“…Astuti, Sudarsono, Sulaeman, & Syukur (2016) explained that the basic concept of organic farming is a method of crop production by avoiding or as much as possible preventing the use of synthetic chemical compounds (fertilizers, pesticides, and growth regulators). Yuriansyah, Dulbari, Sutrisno, & Maksum (2020) in his research revealed that the basic principles of organic agriculture include (1) keeping the ecosystem healthy, (2) applying the principle of efficiency to the cultivation system, (3) carrying out production activities with the concept of sustainable agriculture, (4) producing a pesticide-free product, and (5) preserving the environment. Suparta & Kartini (2001) explained that in the development of organic farming systems there are several principles, one of which is a healthy ecosystem through (a) optimizing the empowerment of natural resources, (b) using environmentally friendly materials, (c) increasing ecosystem diversity; and (d) crop rotation.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Environmentally friendly agricultural practices, also known as organic farming, are currently widely applied in agricultural systems in various countries (Yuriansyah et al, 2020). Public awareness of healthy food has made organic farming practices increasingly intensive.…”
Section: Introductionmentioning
confidence: 99%